FATWA MUI TENTANG PENYELENGGARAAN IBADAH DI MASA PANDEMI COVID 19 - Syafruddin Syafruddin (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2020)
Covid-19 is a new outbreak that is spread in various parts of the world including in Indonesia. Even the World Health Organization (WHO) immediately established Covid-19 as a pandemic. So that Covid-19 is not widespread, it is necessary to have concrete and appropriate steps in the form of preventing and controlling its spread. The Indonesian Ulema Council (MUI) deems it necessary to have a special fatwa stipulation for organizing worship during the Covid-19 pandemic as a guide for Muslims.